Bromoform, dibromochloromethane, and dibromomethane over the East China Sea and the western Pacific Ocean: Oceanic emission and spatial variation. (October 2020) - Liu, Shan-Shan; He, Zhen; Yang, Gui-Peng
Abstract: Spatial distributions of bromocarbons, including bromoform (CHBr3 ), dibromochloromethane (CHBr2 Cl), and dibromomethane (CH2 Br2 ), and influential oceanographic parameters that determine their concentrations were measured in the marine atmosphere and seawater of the East China Sea (ECS) and western Pacific Ocean during two cruises from 14 to 24 September, 2017 and from 5 October to 3 December, 2018. The atmospheric concentrations of CHBr3, CHBr2 Cl, and CH2 Br2 were 0.33–3.02, 0.16–1.96, and 0.85–1.75 pptv over the western Pacific Ocean and 2.23–4.92, 0.26–1.52, and 0.24–7.47 pptv over the ECS, respectively. There was significant spatial variability in atmospheric bromocarbon concentrations in the study region, with higher concentration over the ECS. The atmospheric mixing ratios of bromocarbons were significantly correlated to the surface seawater bromocarbon concentrations and wind speed. In the ECS, input from terrestrial sources also significantly influenced the distributions of bromocarbons in air. PCA analysis revealed that seawater bromocarbon concentrations were correlated with both water mass and chlorophyll a . Generally lower CH2 Br2 /CHBr3 ratios were observed in the ECS, which was indicative of mixing and/or dilution in coastal areas. The estimated average sea-to-air fluxes of CHBr2 Cl, CH2 Br2, and CHBr3 were 46.86,  −3.77, and −6.71 nmol m −2 d −1 in the western Pacific Ocean and 111.49, 0.89, and 321.74 nmol m −2 d −1 in the ECS, respectively. These results of the net sea-to-air fluxes indicated oceanic net uptake of CH2 Br2 and CHBr3 for the western Pacific Ocean and oceanic emission of bromocarbons for the ECS. Highlights: Atmospheric bromocarbons were measured in the western Pacific Ocean and the ECS. Source of atmospheric bromocarbons were significantly affected by wind speed. The elevated atmospheric bromocarbons concentrations were measured over the ECS. Terrestrial sources significantly influenced atmospheric bromocarbon distributions.